Selective autophagy: adding precision in plant immunity. Issue 2 (5th August 2022) - Leong, Jia Xuan; Langin, Gautier; Üstün, Suayib
Abstract: Plant immunity is antagonized by pathogenic effectors during interactions with bacteria, viruses or oomycetes. These effectors target core plant processes to promote infection. One such core plant process is autophagy, a conserved proteolytic pathway involved in ensuring cellular homeostasis. It involves the formation of autophagosomes around proteins destined for autophagic degradation. Many cellular components from organelles, aggregates, inactive or misfolded proteins have been found to be degraded via autophagy. Increasing evidence points to a high degree of specificity during the targeting of these components, strengthening the idea of selective autophagy. Selective autophagy receptors bridge the gap between target proteins and the forming autophagosome. To achieve this, the receptors are able to recognize specifically their target proteins in a ubiquitin-dependent or -independent manner, and to bind to ATG8 via canonical or non-canonical ATG8-interacting motifs. Some receptors have also been shown to require oligomerization to achieve their function in autophagic degradation. We summarize the recent advances in the role of selective autophagy in plant immunity and highlight NBR1 as a key player. However, not many selective autophagy receptors, especially those functioning in immunity, have been characterized in plants. We propose an in silico approach to identify novel receptors, by screening the Arabidopsis proteome for proteins containing features theoretically needed for a selective autophagy receptor. To corroborate these data, the transcript levels of these proteins during immune response are also investigated using public databases. We further highlight the novel perspectives and applications introduced by immunity-related selective autophagy studies, demonstrating its importance in research.